Thrombin Inhibition and Thrombin Generation by Cultured Aortic Endothelial and Smooth Muscle Cells from Minipig - Kirchhof, B; Grünwald, J (Thrombosis and Haemostasis, 1982)
Endothelial and smooth muscle cells cultured from minipig aorta were examined for their inhibitory activity on thrombin and for their thrombin generating capacity.Endothelial cells showed both a thrombin inhibition and an activation of prothrombin in the presence of Ca++, which was enhanced in the presence of phospholipids. Smooth muscle cells showed an activation of prothrombin but at a lower rate. Both coagulation and amidolytic micro-assays were suitable for studying the thrombin-vessel wall interaction.
Keywords: Thrombin generation; Thrombin inhibition; Endothelial cells; Smooth muscle cells